Legal Consequences of Non-Disclosure Agreements Between Companies and Employees Regarding the Protection of Sales Methods as Trade Secrets - Lemmy, Muhammad Ilham Akbar; Siregar, Mahmul; Robert, Robert (DE LEGA LATA: JURNAL ILMU HUKUM, 2025)
The use of NDAs can certainly be employed as a preventive measure against the disclosure of trade secrets. An NDA is an agreement or contract used to protect a company's confidential information from being leaked. This research discusses the issue: What is the legal standing of NDAs in protecting a company's trade secrets from the perspective of Indonesian law? What are the legal consequences of NDAs between companies and employees regarding the protection of sales methods as trade secrets?This study uses a normative legal research method with a conceptual approach, a legislative approach, and an analytical approach. The research is descriptive in nature. The legal materials used include primary legal materials, namely Law of the Republic of Indonesia No. 30 of 2000 concerning Trade Secrets, and secondary legal materials.The results of this study indicate the urgency of creating NDAs between companies and employees in production or service sectors that regulate the boundaries of trade secrets prohibited from being disclosed to the public, thereby ensuring legal certainty between the parties. The impact of this will result in losses for the company and may lead to legal consequences in the form of civil sanctions causing compensation and criminal sanctions resulting in imprisonment and fines.Keywords: Legal Consequences, NDA, Company, Sales Methods, Secrets Trade.